Retrograde recanalization of radial artery occlusion via the distal transradial artery: A single-center experience - Lin, Yaowang; Bei, Weijie; Liu, Huadong; Liu, Qiyun; Yuan, Jie; Wu, Meishan; Sun, Xin; Dong, Shaohong (Frontiers in Cardiovascular Medicine, 2022)
Background: Radial artery occlusion (RAO) often occurs after catheterization when using a transradial artery approach. Objective: This prospective study assessed the success and feasibility of accessing the distal transradial artery (dTRA) for retrograde recanalization of RAO. Methods: From June 2019 to December 2021, 44 consecutive patients who had undergone cardiac catheterization resulting in RAO were given retrograde recanalization via the dTRA. According to the result of the procedure (primary endpoint), patients’ cases were analyzed as successful or failed. Rates of post-operative patency and adverse events were calculated up to 12 months. Results: The procedural success rate was 88.6%. Compared with the successful group, a significantly higher percentage of patients in the failed group were current smokers and/or suffered from diabetes mellitus (each, 80.0% cf. 33.3%, P = 0.046); had undergone at least 3 previous cardiac catheterizations (60.0% cf. 12.8%, P = 0.011), and exhibited chronic total occlusion (100.0% cf. 51.28%, P = 0.041). In each group, one patient each had minor bleeding at the access site and hematoma. The patency rates in the successful group at postoperative 3, 6, and 12 months were 48.7, 43.6, and 35.9%, respectively. Conclusion: The dTRA approach for retrograde recanalization of RAO showed a high procedural success rate, but with patency rates of less than 50% at follow-up.